Physiological seed priming techniques in millets - Dheeravathu, Seva Nayak; Srividhya, S; Swarna, R; Singode, Avinash (Indian Farming, 2023)
In recent years, various strategies are being employed in order to induce the abiotic stress tolerance in plants. It is well accepted fact that physiological seed priming fastens the germination time. It is an effective, practical and facile technique to enhance uniform emergence, seedling vigour and yields in millets, particularly under rainfed or less fertile soils. Seed priming is a broad term but in this article, physiological seed priming techniques, viz. hydro-priming, osmo-priming, hormonal priming, nutrient priming and nano-priming have been discussed in detail as these techniques are cost effective, ecofriendly and simple.